Association of FV G1691A, FV H1299R, and FII G20210A variations with thrombosis and coronary artery disease (CAD): A population-based study - Ünallı Özmen Sevda; Özarda Yeşim; Köseler Aylin; Sabırlı Ramazan; Kaynak Derya Sucu; Koç Ibrahim (Journal of Medical Biochemistry)
Background: Thrombosis and coronary artery disease (CAD) are complex disorders influenced by genetic factors. Specific gene variations, such as Factor V (FV) G1691A (Leiden), FV H1299R, and Prothrombin (FII) G20210A, have been implicated in thrombotic events and CAD. However, their precise role in CAD development remains controversial. This study investigated the prevalence and association of these gene variations with thrombosis and CAD in the Turkish population. Methods: A case-control study included 406 healthy individuals and 64 CAD patients. Genotyping for FV G1691A, FV H1299R, and FII G20210A was performed using a strip assay. Fisher's exact test compared allele and genotype frequencies between the CAD and control groups. Results: No significant differences were observed in genotype frequencies of FV G1691A, FV H1299R, and FII G20210A between the CAD and control groups (p>0.05). Similarly, allele frequencies did not differ significantly between the two groups (p>0.05). Conclusions: The findings suggest that FV G1691A, FV H1299R, and FII G20210A variations may not play a significant role in the development of CAD in the Turkish population studied. These results are consistent with the existing conflicting literature on the association between these gene variations and CAD. Further research with larger sample sizes and diverse populations is warranted to elucidate the role of these variations in CAD pathogenesis.